Vulnerability and autonomy. Theoretical considerations based on children's narrations about sport in adult-dominated contexts - Catrin Heite; Veronika Magyar-Haas; Lea Moser; Marion Pomey; Morad Salah; Franziska Schlattmeier (Social Work & Society, 2020)
Starting from the perspective of the new social studies of childhood and their strong focus on agency of children this article follows the critical voices on the agency concept and reconceptualises children's autonomy under conditions of vulnerability. Within the adult dominated field of sport the phenomenon of children's vulnerability as well as children's autonomy can be seen and discussed empirically. The authors analyse what and how children's autonomy is enabled or limited e.g. through organisational aspects or through the superior position of adults. This leads to new findings concerning children's emotional and physical vulnerability, children's decisions about leisure time and adult-free spaces as well as the limitation of children's autonomy. As a conclusion or in the sense of an outlook, thoughts towards theories of professionalism are considered.